2020
DOI: 10.1161/circ.142.suppl_3.14264
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 14264: The Impact of Bariatric Surgery on Echocardiographic Features of Cardiac Remodeling and Diastolic Function

Abstract: Introduction: Candidates for bariatric surgery are at increased risk for cardiovascular disease and often develop adverse cardiac remodeling as a result of obesity. Bariatric surgery can alter cardiac structure and function in these patients; however, this has not been fully investigated. Hypothesis: We hypothesized that patients undergoing bariatric surgery would demonstrate favorable cardiac remodeling and improvement in diastolic parameters according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…29 An American Society of Echocardiography study in 2020 which looked at the impact of bariatric surgery on the echocardiographic features of cardiac remodeling and diastolic function concurred with our findings: patients with pre-existing diastolic dysfunction demonstrated improvements in diastolic function, driven by changes in TR velocity and medial E/e'. 30 The advent of strain imaging echocardiography now offers a readily available and portable imaging tool that not only offers an objective characterization of myocardial dynamics but also allows for early detection of subclinical left ventricular dysfunction. Multiple studies have shown a direct correlation between obesity and GLS pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 An American Society of Echocardiography study in 2020 which looked at the impact of bariatric surgery on the echocardiographic features of cardiac remodeling and diastolic function concurred with our findings: patients with pre-existing diastolic dysfunction demonstrated improvements in diastolic function, driven by changes in TR velocity and medial E/e'. 30 The advent of strain imaging echocardiography now offers a readily available and portable imaging tool that not only offers an objective characterization of myocardial dynamics but also allows for early detection of subclinical left ventricular dysfunction. Multiple studies have shown a direct correlation between obesity and GLS pattern.…”
Section: Discussionmentioning
confidence: 99%
“… 29 An American Society of Echocardiography study in 2020 which looked at the impact of bariatric surgery on the echocardiographic features of cardiac remodeling and diastolic function concurred with our findings: patients with pre-existing diastolic dysfunction demonstrated improvements in diastolic function, driven by changes in TR velocity and medial E/e’. 30 …”
Section: Discussionmentioning
confidence: 99%